ECONOMIC SUBSIDIES IN AGRICULTURE - Babić, Violeta; Milošević, Božidar; Maksimović, Goran (Economics of Agriculture, 2015)
The funds allocated to agriculture are a signifcant part of economic transfers. A large part of the EU budget is directed to agriculture, and the average amount of subsidies in the EU- 27 was, in 2013, approximately € 330 per hectare. Agriculture subsidies comprise about 60% of total subsidies in the EU. Situation in Serbia is not as good as in the EU because the subsidies per hectare are three times lower, and a subsidy to agriculture stands slightly above 30% of total subsidies, but with a tendency to increase over the past two years. This paper, through a comparative analysis of public expenditures for agriculture in Serbia and the EU countries (both developed countries and the countries in our immediate surroundings), shows the relevance and importance given to agriculture, due to its development opportunities. Serbian agriculture can be the engine of economic development and this is supported by the fact that the projection of expenditures for agriculture in the medium term has a tendency to rise.